Utilizing hydrothermal time models to assess the effects of temperature and osmotic stress on maize (Zea mays L.) germination and physiological responses - Waqif Khan; Sumbal Shah; Abd Ullah; Sami Ullah; Fazal Amin; Babar Iqbal; Naveed Ahmad; Mostafa A. Abdel-Maksoud; Mohammed k. Okla; Mohamed El-Zaidy; Wahidah H. Al-Qahtani; Shah Fahad (BMC Plant Biology, 2023)
Abstract The application of germination models in economic crop management makes them extremely useful for predicting seed germination. Hence, we examined the effect of varying water potentials (Ψs; 0. − 0.3, − 0.6, − 0.9, − 1.2 MPa) and temperatures (Ts; 20, 25, 30, 35, 40 °C) on maize germination and enzymatic antioxidant mechanism. We observed that varying Ts and Ψs significantly influenced germination percentage (GP) and germination rate (GR), and other germination parameters, including germination rate index (GRI), germination index (GI), mean germination index (MGI), mean germination time (MGT), coefficient of the velocity of germination (CVG), and germination energy (GE) (p ≤ 0.01). Maximum (87.60) and minimum (55.20) hydro-time constant (θH) were reported at 35 °C and 20 °C, respectively. In addition, base water potential at 50 percentiles was highest at 30 °C (15.84 MPa) and lowest at 20 °C (15.46 MPa). Furthermore, the optimal, low, and ceiling T (To, Tb and Tc, respectively) were determined as 30 °C, 20 °C and 40 °C, respectively. The highest θT1 and θT2 were reported at 40 °C (0 MPa) and 20 °C (− 0.9 MPa), respectively. HTT has a higher value (R2 = 0.43 at 40 °C) at sub-optimal than supra-optimal temperatures (R2 = 0.41 at 40 °C). Antioxidant enzymes, including peroxidase (POD), catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), and glutathione peroxidase (GPX), increased with decreasing Ψs. In contrast, CAT and POD were higher at 20 °C and 40 °C but declined at 25, 30, and 35 °C. The APX and GPX remained unchanged at 20, 25, 30, and 40 °C but declined at 35 °C. Thus, maintaining enzymatic activity is a protective mechanism against oxidative stress. A decline in germination characteristics may result from energy diverting to anti-stress tools (antioxidant enzymes) necessary for eliminating reactive oxygen species (ROS) to reduce salinity-induced oxidative damage. The parameters examined in this study are easily applicable to simulation models of Z. mays L. germination under extreme environmental conditions characterized by water deficits and temperature fluctuations.